Alga-based mathematical model of a life support system closed in oxygen and carbon dioxide - D. A. Semyonov; A. G. Degermendzhi (Вавиловский журнал генетики и селекции)
The purpose of the study was to compare quantitative analysis methods used in the early stages of closed-loop system prototyping with modern data analysis approaches. As an example, a mathematical model of the stable coexistence of two microalgae in a mixed flow culture, proposed by Bolsunovsky and Degermendzhi in 1982, is considered. The model is built on the basis of a detailed theoretical description of the interaction between species and substrate (in this case, illumination). The ability to control the species ratio allows you to adjust the assimilation quotient (AQ), that is, the ratio of carbon dioxide absorbed to oxygen released. The problem of controlling the assimilation coefficient of a life support system is still relevant; in modern works, microalgae are considered as promising oxygen generators. At the same time, modern works place emphasis on empirical modeling methods, in particular, on the analysis of big data, and the work does not go beyond the task of managing a monoculture of microalgae. In our work, we pay attention to three results that, in our opinion, successfully complement modern methods. Firstly, the model allows the use of results from experiments with monocultures. Secondly, the model predicts the transformation of data into a form convenient for further analysis, including for calculating AQ. Thirdly, the model allows us to guarantee the stability of the resulting approximation and further refine the solution by small corrections using empirical methods.